Ultrasound and CT Equivalent in Suspected Kindney Stone – an Impetus to Rethink - Seitz, K. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
An innovative, prospective, randomized multicenter study regarding the diagnosis of kidney stones with ultrasound and CT including more than 2700 patients was recently published in the highly respected New England Journal of Medicine 1. The study showed that in the case of clinical suspicion of nephrolithiasis the results of those primarily examined with ultrasound and those primarily examined with CT did not differ with respect to diagnoses, complications, pain, frequency of repeat presentation at the emergency room and hospitalization over 30 days, and not even with respect to missed diagnoses during a 6-month follow-up period. For the detection of kidney stones, there were as slightly lower sensitivity and a higher specificity for US compared to CT.As expected, the radiation exposure and costs in the ultrasound arm were lower. Approximately 40 % of the ultrasound patients underwent CT in the following 6 months. The study results are certainly surprising to many colleagues who saw unenhanced low-dose CT as the diagnostic gold standard in a strict method comparison 23. No wonder that the frequency of CT examinations for suspected kidney stones has increased in the USA tenfold from 1996 – 2007 4.However, in light of earlier ultrasound publications regarding kidney stone diagnosis, this result is not surprising. The importance of ultrasound for kidney stone diagnosis 56 and the equivalence of US and intravenous urography even for the detection of ureteral stones have long been known in Europe 789. We know even German publications cannot be widely read and even English publications require an accepted publication medium or they remain virtually unknown. A prospective study including 100 patients in the discontinued EJU publication from Elsevier showed equivalence of ultrasound and intravenous urography for kidney and ureteral stones and superiority of US over plain radiography of the kidneys 9. Today, numerous studies are available, primarily comparisons between US and CT with very different results. As in the past, the results primarily depend on the quality of the examination technique 101112131415.The study by Smith-Bindman et al. 1 shows the high value of ultrasound diagnosis when used directly in the clinical setting. The concept of continuing the physical examination with technical means was introduced in Germany in 1976 16. The additional inclusion of the medical history was performed as part of “clinical sonography” in Europe. This approach was named “point of care ultrasound” in the USA and for approximately 15 years American colleagues in emergency units have been using the ultrasound probe with great success in this regard.In the USA this new development was based less on European experiences than on increasing economic pressure and the rapid development of US equipment. The discussion regarding CT-based increased radiation exposure and the possible increase in malignant diseases that was started by Brenner et al. 17 and is still ongoing may have also had an impact. This discussion has basically not yet reached Germany.What can we learn from this new study?The study in NEJM should provide the impetus for the primary use of ultrasound in the case of clinical suspicion of nephrolithiasis. The majority of the use of CT and excretory urography could be decreased by approximately 80 % for this common medical problem, thus making a significant contribution to radiation hygiene.Moreover, we can learn how to perform excellent, clinically relevant studies with cooperation and relatively simple means. To ensure a high level of significance for ultrasound diagnostics, more clinical and sonografic competence and intensive ultrasound training is necessary. In addition, we need a greater number of significant studies that should be published as prominently as possible.